I Fail; Therefore, I Can: Failure Mindset and Robotics Self-Efficacy in Early Adolescence - Calah J. Ford; Margaret J. Mohr-Schroeder; Ellen L. Usher (MDPI AG, 2023)
When students feel successful, they tend to be more confident in their capabilities (i.e., higher self-efficacy), which is associated with improved performance, engagement, and self-regulation. Yet, the way in which learners interpret their experiences is less well-understood. Learners' views of failure (i.e., failure mindset) are potential lenses through which early adolescent learners perceive and interpret efficacy-relevant information. The relationship between failure mindset and self-efficacy may be particularly important to consider in STEM-related domains like robotics where failure is common. The purpose of this study was to investigate the relationship between young adolescents' failure mindset and their robotics self-efficacy development. Using mixed methods, we considered how students' reported failure mindset levels were related to what has made them more or less confident in robotics. We also considered the relationship between failure mindset and robotics self-efficacy. Overall, the findings suggest that early adolescent learners' failure mindset is related to the efficacy-relevant information they pay attention to in robotics, and, in turn, is associated with their reported robotics self-efficacy. The details of these relationships varied between elementary and middle school students. As there is a social push to normalize failures in educational settings, findings from this study offer an important insight into how students may interpret those failures.